Smokers' knowledge and perception of electronic cigarettes (e-cigarettes): a qualitative study of non-quitting smokers in a North London general practice. (2nd July 2019) - Vasconcelos, Vanessa; Gilbert, Hazel
Abstract: Background: The introduction of electronic cigarettes (e-cigarettes) has provided smokers with an alternative source of nicotine. Interest and use of the device has increased exponentially in the last decade with an estimated 2.9 m adult users in Great Britain. Research so far on the attitudes and perceptions of smokers to this new product has largely focussed on the views of current e-cigarette users, smokers attempting to quit and former cigarette smokers. Aim: This study aimed to explore the views of current tobacco smokers who were not using e-cigarettes and not looking for a cessation method, their understanding and knowledge of e-cigarettes, and their views of e-cigarettes as a smoking cessation aid provided by the National Health Service (NHS). Methods: Semi-structured in-depth interviews were conducted with 14 patients from a general practice in North London, who smoked conventional tobacco cigarettes on a daily or weekly basis, over 18 years old. An iterative approach allowed for constant data analysis using a thematic approach throughout the data collection stage, and generated four recurring themes. Findings: E-cigarettes were primarily seen as a smoking cessation device, with the supply of nicotine viewed as a benefit helping to reduce withdrawal symptoms, although for some participants this supply could also be a hindrance to dealing with their addiction. Despite uncertainty about the components, e-cigarettes were mostly viewed as healthier due to their lack of carcinogens, tar and smoke inhalation. The lack of reliable information and strong evidence for both the effectiveness and the safety of e-cigarettes led participants to be apprehensive about their provision by the NHS, and acted as a barrier to their use as an aid to quitting. The recurring appeal for more information regarding e-cigarettes make it clear that further high-quality research is urgently needed in this field to provide reliable and accurate information to smokers.